POSSIBILITIES OF DRIED DISTILLERS’ GRAINS WITH SOLUBLES APPLICATION IN FEED MIXTURES - Nikolić, Valentina; Milašinović-Šeremešić, Marija; Radosavljević, Milica; Simić, Marijana; Žilić, Slađana; Vančetović, Jelena; Božinović, Sofija (Journal on Processing and Energy in Agriculture, 2021)
The possibility of utilization of dried distiller’s grains with solubles (DDGS) in feed mixtures for feed production was investigated. Samples of maize hybrids ZP 548 and ZP 655b and DDGS obtained from hybrids ZP 548 and ZP 548c were used as components of the mixtures.The total protein content ranged from 12.42 % to 31.18 %, moisture from 5.49 % to 9.55 and ash content of 1.85 % to 4.37 %. The contents of NDF, ADF, ADL, hemicellulose and cellulose fibers ranged from: 13.90 % to 48.13 %; 2.96 % to 20.69 %; 0.27 % to 2.44 %; 10.69 % to 30.17 %, 2.62 % to 18.32 %, respectively. In vitro dry matter digestibility ranged from 55.20 % to 89.76 %. It was concluded that the samples of DDG obtained from red and yellow maize hybrids kernel are very suitable as components for the preparation of animal feed mixtures.